Heteroatom‐Doped Mesoporous Hollow Carbon Spheres for Fast Sodium Storage with an Ultralong Cycle Life. Issue 19 (26th March 2019) - Ni, Dan; Sun, Wang; Wang, Zhenhua; Bai, Yu; Lei, Hongshuai; Lai, Xinhua; Sun, Kening
Abstract: Carbon materials have attracted significant attention as anode materials for sodium ion batteries (SIBs). Developing a carbon anode with long‐term cycling stability under ultrahigh rate is essential for practical application of SIBs in energy storage systems. Herein, sulfur and nitrogen codoped mesoporous hollow carbon spheres are developed, exhibiting high rate performance of 144 mA h g −1 at 20 A g −1, and excellent cycling durability under ultrahigh current density. Interestingly, during 7000 cycles at a current density of 20 A g −1, the capacity of the electrode gradually increases to 180 mA h g −1 . The mechanisms for the superior electrochemical performance and capacity improvement of the cells are studied by electrochemical tests, ex situ transmission electron microscopy, X‐ray diffraction, X‐ray photoelectron spectroscopy, and Raman analysis of fresh and cycled electrodes. The unique and robust structure of the material can enhance transport kinetics of electrons and sodium ions, and maintain fast sodium storage from the capacitive process under high rate. The self‐rearrangement of the carbon structure, induced by continuous discharge and charge, lead to the capacity improvement with cycles. These results demonstrate a new avenue to design advanced anode materials for SIBs. Abstract : Interconnected hollow carbon spheres with mesopores and heteroatom doping are prepared. When used as anode for sodium ion batteries, the material, whose unique and robust structure can enhance the transport kinetics of electrons and sodium ions, maintains fast sodium storage under high rate, guarantees the structure stability during long‐term cycling, and exhibits excellent electrochemical performance.